Severe immune thrombocytopenia (ITP) following SARS-CoV-2 mRNA vaccine in a girl on immunosuppressive treatment and in prolonged stable phase of ITP. - SIMONA BIANCHI; ALESSIA ANGI; MAURO PASSUCCI; GIOVANNA PALUMBO; ERMINIA BALDACCI; ANNA MARIA TESTI (Mediterranean Journal of Hematology and Infectious Diseases)
Rare cases of immune thrombocytopenia (ITP) occurring after SARS-CoV-2 mRNA vaccines have recently reached public attention. It has been reported in patients with previous ITP or other autoimmune diseases and in individuals with an apparent negative past medical history.  The management and the outcome of these cases are still not well investigated and reported in the medical literature. A 23-year-old female with a past medical history of ITP, in stable complete remission for 3 years and on mycophenolate treatment received SARS-CoV-2 mRNA vaccine. She presented severe ITP recurrence with hemorrhagic symptoms after the second vaccine dose. A combined treatment with high-dose immunoglobulin and prednisone was successfully administered with a full recovery of platelet count. The patient remains in ITP remission and on mycophenolate therapy, five months later. At our Center, none of the other 76 adult “fragile patients” with ITP on immunosuppressive treatment who had received the SARS-CoV-2 mRNA vaccine, developed such a severe thrombocytopenic recurrence. Follow-up of large cohorts of patients receiving mRNA vaccine will answer the question as to whether it increases the risk of autoimmune conditions. So far, the benefits of the vaccination largely outweigh the risk of infection in these patients.